Socio-economic implications and environmental effects of oil spillage in some communities in the Niger Delta (2009)
This study examined the effects of oil spillage on the socio-economic activities of the people and the environment in some communities in the Niger delta. The objectives are to determine the quantity of oil spilled from pipelines, the area of coverage and to assess the effects of oil spillage on the people, soil and water. Data were collected from both primary and secondary sources. The primary data relied on the administration of structured questionnaires; 319 questionnaires were randomly distributed to a sample population (household heads), with 302 retrieved. Secondary data were sourced from published materials. Also, soil samples from four locations and water samples from five locations were collected to determine the pH value of the water, the presence and concentration of heavy metals in the soil and the total hydrocarbon content (THC) of water. Soil and water samples were analysed using the atomic absorption spectrophotometer and gravimetric methods for soil and water, respectively. There was a strong relationship between the volume of oil spilled and the area coverage. Laboratory soil analysis from sampled communities showed a higher concentration of heavy metals (chromium, lead, arsenic, etc.) above the World Health Organization (WHO) permissible levels as well as the figure for controlled site. Similarly, three of the communities studied had THC concentrations of 40,000 ppm exceeding both WHO limit of 1 ppm and controlled site. This has grave implications on the soil, water and socio-economic activities of the people. It is, therefore, important that environmental laws should be strictly adhered to. Compensation should be adequately and promptly paid to the communities, and remedial action should be speedily undertaken whenever there are spills. Finally, the oil companies must involve the communities in the maintenance and monitoring of pipelines with the ultimate goal of improving the quality of life of members of rural communities.